Fluid mechanical modeling of the upper urinary tract. Issue 6 (14th March 2021) - Zheng, Shaokai; Carugo, Dario; Mosayyebi, Ali; Turney, Ben; Burkhard, Fiona; Lange, Dirk; Obrist, Dominik; Waters, Sarah; Clavica, Francesco
Abstract: The upper urinary tract (UUT) consists of kidneys and ureters, and is an integral part of the human urogenital system. Yet malfunctioning and complications of the UUT can happen at all stages of life, attributed to reasons such as congenital anomalies, urinary tract infections, urolithiasis and urothelial cancers, all of which require urological interventions and significantly compromise patients' quality of life. Therefore, many models have been developed to address the relevant scientific and clinical challenges of the UUT. Of all approaches, fluid mechanical modeling serves a pivotal role and various methods have been employed to develop physiologically meaningful models. In this article, we provide an overview on the historical evolution of fluid mechanical models of UUT that utilize theoretical, computational, and experimental approaches. Descriptions of the physiological functionality of each component are also given and the mechanical characterizations associated with the UUT are provided. As such, it is our aim to offer a brief summary of the current knowledge of the subject, and provide a comprehensive introduction for engineers, scientists, and clinicians who are interested in the field of fluid mechanical modeling of UUT. This article is categorized under: Cancer > Biomedical Engineering Infectious Diseases > Biomedical Engineering Reproductive System Diseases > Biomedical Engineering Abstract : Illustration of the urinary tract under various physiological and pathological conditions.